2006
DOI: 10.1111/j.1749-7345.2006.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Supplementation of All‐plant Protein Diets for Rainbow Trout (Oncorhynchus mykiss)

Abstract: Abstract.— Taurine has been demonstrated to be conditionally indispensable for several carnivorous fish species. Current trends in trout production include decreasing levels of fish‐meal content in feeds, along with faster growing strains of fish. Taurine may be a limiting nutrient in support of elevated planes of growth for rainbow trout. A 9‐wk feeding trial was conducted using a factorial treatment design with protein source (fish meal or plant) and taurine supplementation (four levels) as the main effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
144
8
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(169 citation statements)
references
References 24 publications
15
144
8
2
Order By: Relevance
“…However, these values are much lower than those from other studies which fed soybean meal or other soybean products [48,50,52,53]. The only significant decrease in HSI observed in the current study was in the fish which received all of their protein from PSG.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…However, these values are much lower than those from other studies which fed soybean meal or other soybean products [48,50,52,53]. The only significant decrease in HSI observed in the current study was in the fish which received all of their protein from PSG.…”
Section: Discussioncontrasting
confidence: 88%
“…In many of these other studies, fish meal-based control diets were not used, or the concentrations of other non-soy protein sources were altered in the experimental diets [14][15][16]24,[48][49][50][51][52][53]. However, Barrows et al [54] suggested that soybean meal replacement for fish meal should be limited to less than 25% (or 10% to 15% dietary inclusion rates).…”
Section: Discussionmentioning
confidence: 99%
“…The reduced methionine intake, and the lower liver taurine, resulted in higher accumulation of lipid in the liver while lysine limitations increased the lipid concentration in the whole fish (Espe et al, 2007). Also in the rainbow trout the methionine and taurine was found to affect the lipid deposition, but methionine rather than taurine was responsible (Gaylord et al, 2007). In juvenile Atlantic salmon we reported that taurine supplementation to plant protein based diets reduced the whole body lipid deposition without affecting protein deposition .…”
Section: Future Aspectsmentioning
confidence: 83%
“…Methionine is one of the most essential amino acid that becomes a limiting factor in diet [28]. Methionine deficiency in diet can inhibit transcription process, which inhibits some enzyme formation [29]. The high content of methionine in ED2 is thought to be the reason for the high survival during culture period, considering that methionine has many roles related with regulation and metabolic pathway mediating [29].…”
Section: Growth and Survival Parametersmentioning
confidence: 99%
“…Methionine deficiency in diet can inhibit transcription process, which inhibits some enzyme formation [29]. The high content of methionine in ED2 is thought to be the reason for the high survival during culture period, considering that methionine has many roles related with regulation and metabolic pathway mediating [29]. Beside methionine, lysine often becomes one of the most limiting amino acid in commercial fish diet [28].…”
Section: Growth and Survival Parametersmentioning
confidence: 99%